[River Lined With Basalt Rock] - Streng, Evelyn Fiedler (1975)
Photograph of a river lined with basalt rock in Iceland. The blue river cuts through the green landscape. Grey rock sits on the edge of the water and around a small, white building with a green roof. An Icelandic flag flies above the building on the right. A stone platform sits beside the water to the left, attached to a raised road where vehicles sit. A mountain range is visible in the far distance.